Knossos and the Near East : a contextual approach to imports and imitations in early Iron Age tombs - Antoniadis, Vyron, (Archaeopress Publishing Ltd, 2017)
In this work, Dr Vyron Antoniadis presents a contextual study of the Near Eastern imports which reached Crete during the Early Iron Age and were deposited in the Knossian tombs.